齿轮与轴压装过程过盈配合研究 - 何亚峰; 杨小斌; 干为民 (Jixie chuandong)
Due to the characteristics of good load capacity and simple structure etc,the interference fit is widely used in practice production.Because the assembly interference quantity between gear and shaft directly affects the working performance of gear transmission,it is important significance for studying the gear and axis interference fit.The calculation format of interference fit quantity is obtained by deriving theoretically the interference fit process of gear and axis.At the same time,the numerical calculation of the maximum amount of interference between gear and axis is carried out by using finite element method,the variation of stress distribution and fitting force is obtained.The results show that the theoretical calculation and finite element calculation are basically consistent,and a certain theory and basis for gear and axis interference design is provided and has important practical value.